FIKIH INDONESIA: EPISTEMOLOGI SOSIO-KULTURAL - Mahfudz Junaedi (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2018)
Abstract Fiqh presents with the presence of Islamic studies that then isbeing practiced in the society. Fiqh epistemology in Indonesia asthe Islamic law has characters and Indonesian special featureseither written or unwritten in the book of law. All this time, fiqh isstill attached with cultural trademark and Middle-Eastern tradition.The socio-cultural condition of Indonesia society, however, givescontribution and historical setting of Islamic law in Indonesia sothat fiqh reformation that is identical with Indonesian is thedemand and the dynamic of modern Muslims nowadays. Fiqh as anecessity must be kept in touch with science as the integral partand takes into account to solve the modern problems through theupdate thought to form the Indonesian fiqh. The indigenization offiqh holistically uses the various patterns and methods. Thedemand of updating fiqh already causes the reshuffle of fiqhepistemology from teosentrisme epistemology to antroposentrismeepistemology. Therefore, the contextualization of fiqh alwaysfollows the socio-cultural and development of human knowledgewith various typology characteristics of society that are formed byits socio-culture and the culture around it. Hence, fiqh will befresher than before to answer the new problems in modern societyin Indonesian context.